Divergent Evolution of Male Aggressive Behaviour: Another Reproductive Isolation Barrier in Extremophile Poeciliid Fishes?. (23rd January 2012) - Bierbach, David; Klein, Moritz; Sassmannshausen, Vanessa; Schlupp, Ingo; Riesch, Rüdiger; Parzefall, Jakob; Plath, Martin
Abstract : Reproductive isolation among locally adapted populations may arise when immigrants from foreign habitats are selected against via natural or (inter-)sexual selection (female mate choice). We asked whether also intrasexual selection through male-male competition could promote reproductive isolation among populations of poeciliid fishes that are locally adapted to extreme environmental conditions [i.e., darkness in caves and/or toxic hydrogen sulphide (H2 S)]. We found strongly reduced aggressiveness in extremophile Poecilia mexicana, and darkness was the best predictor for the evolutionary reduction of aggressiveness, especially when combined with presence of H2 S. We demonstrate that reduced aggression directly translates into migrant males being inferior when paired with males from nonsulphidic surface habitats. By contrast, the phylogenetically old sulphur-endemic P. sulphuraria from another sulphide spring area showed no overall reduced aggressiveness, possibly indicating evolved mechanisms to better cope with H2 S.